Dynamic response of a high-rise chemical tower controlled by pseudo-elastic shape memory alloy cables. (June 2016) - Sun, Shuangshuang; Lv, Mei
The wind-induced vibration of a high-rise chemical tower controlled by pseudo-elastic shape memory alloy cables was studied in this work. Based on taking into account phase transformations of shape memory alloy, the motion equation of the shape memory alloy–controlled chemical tower was established by the finite element method, which was coupled with phase transformation equations of shape memory alloy. The incremental finite-element-based Newmark integration method and the iterative method were utilized to solve this motion equation, and the dynamic response of the shape memory alloy–controlled chemical tower was analyzed. The results were compared with those of the chemical tower without any cables and under the control of common cables. It is found that pseudo-elastic shape memory alloy cables have good vibration suppression effect on the chemical tower. In addition, the vibration suppression effect of shape memory alloy cables is affected by the operating temperature, initial pre-strain of shape memory alloy, cross-sectional size of shape memory alloy, and the angle between each shape memory alloy cable and the ground.